Cellular uptake and antitumor activity of DOX-hyd-PEG-FA nanoparticles. - Wei-liang Ye (Public Library of Science (PLoS), 2014)
A PEG-based, folate mediated, active tumor targeting drug delivery system using DOX-hyd-PEG-FA nanoparticles (NPs) were prepared. DOX-hyd-PEG-FA NPs showed a significantly faster DOX release in pH 5.0 medium than in pH 7.4 medium. Compared with DOX-hyd-PEG NPs, DOX-hyd-PEG-FA NPs increased the intracellular accumulation of DOX and showed a DOX translocation from lysosomes to nucleus. The cytotoxicity of DOX-hyd-PEG-FA NPs on KB cells was much higher than that of free DOX, DOX-ami-PEG-FA NPs and DOX-hyd-PEG NPs. The cytotoxicity of DOX-hyd-PEG-FA NPs on KB cells was attenuated in the presence of exogenous folic acid. The IC50 of DOX-hyd-PEG-FA NPs and DOX-hyd-PEG NPs on A549 cells showed no significant difference. After DOX-hyd-PEG-FA NPs were intravenously administered, the amount of DOX distributed in tumor tissue was significantly increased, while the amount of DOX distributed in heart was greatly decreased as compared with free DOX. Compared with free DOX, NPs yielded improved survival rate, prolonged life span, delayed tumor growth and reduced the cardiotoxicity in tumor bearing mice model. These results indicated that the acid sensitivity, passive and active tumor targeting abilities were likely to act synergistically to enhance the drug delivery efficiency of DOX-hyd-PEG-FA NPs. Therefore, DOX-hyd-PEG-FA NPs are a promising drug delivery system for targeted cancer therapy.